Restoration of Buildings and Monuments : Materials science, Conservation of architectural heritage, Sustainable construction (Birkhäuser, 1995)
Restoration of Buildings and Monuments (RBM), publishes invited review articles, original papers, and short communications in the wide field of durability, maintenance and restoration of buildings, structures, and monuments. Contributions present recent results from original research and new experiences from practice.